Pengaruh Financial Management Behavior terhadap Financial Well-Being Penerima Bantuan Program Keluarga Harapan di Kecamatan Paleteang Kabupaten Pinrang - Fitriani Hakim; Darmianti Razak (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
The target beneficiaries of the Family Hope Program (PKH) are impoverished and vulnerable families or individuals. The distribution of assistance under the Family Hope Program in Paleteang District, Pinrang Regency, has not been effective or in accordance with the established guidelines. This study aims to assess the relationship between Financial Management Behavior and the Financial Well-Being of Family Hope Program beneficiaries in Paleteang District, Pinrang Regency, and to examine the impact of Financial Management Behavior on the Financial Well-Being of these beneficiaries in the same area. The research method used is a quantitative approach with an associative approach, employing field research through surveys or questionnaires. The data is analyzed using descriptive analysis, data quality tests, classical assumption tests, correlation tests, hypothesis tests, and simple regression analysis. The results of this study indicate that Financial Management Behavior has a positive and significant relationship with the Financial Well-Being of Family Hope Program beneficiaries in Paleteang District, Pinrang Regency. This is evidenced by a Pearson correlation value of 0.564 with a significance value of 0.000, indicating that the two variables have a moderate, positive, and significant correlation. Furthermore, Financial Management Behavior significantly affects Financial Well-Being, as demonstrated by a t-value greater than the t-table value (6.694 > 1.985) with a significance value of 0.000, which is less than 0.05.